Iconic communication - Yazdani, Masoud; Yazdani, Masoud; Barker, Philip (NBN International, 2000)
Our society is becoming a more visual culture day-by-day. This book offers detailed analyses of how to combine words with pictures to communicate clearly across cultural barriers. While some information is better communicated by one kind of media than another, some information is communicated most effectively through a combination of media. This book presents a critical framework within which iconic communication systems can be developed to truly bridge linguistic and cultural gaps and to provide effective computer-based systems for conveying information on a global scale. With valuable insights for the Information and Communication industries, this book draws on the work presented at several conferences on the subject and is designed primarily for graphic designers and human-computer interface developers as well as supplementary reading on degree courses in Information Technology.